Choline chloride based ionic liquids containing nickel chloride: Physicochemical properties and kinetics of Ni(II) electroreduction. (10th August 2017) - Kityk, A.A.; Shaiderov, D.A.; Vasil'eva, E.A.; Protsenko, V.S.; Danilov, F.I.
Highlights: Physicochemical and electrochemical properties of ethaline + NiCl2 ·6H2 O solutions. Obtained results are interpreted within the framework of hole theory. Irreversible electrochemical behavior of Ni(II)/Ni system. Transport behavior cannot be explained in terms of classical model of diffusion. Formal activation energy of charge transfer Ni(II)→Ni in ethaline is determined. Abstract: The effect of Ni(II) salt content in ethaline (a deep eutectic solvent containing a mixture of ethylene glycol and choline chloride) on density, surface tension, viscosity and conductivity of ionic liquids has been investigated in the temperature range of 25 to 80 °C. The introduction of NiCl2 ·6H2 O into ethaline (ca. 0.1–1 mol dm −3 Ni(II)) causes an increase in the density, surface tension and viscosity of solutions and a decrease in their conductivity. The obtained results are explained in terms of hole theory. Both the electrical conductivity and the viscosity of ionic solutions under consideration are controlled by the availability of suitably sized holes in the liquid. The cyclic voltammetry study performed on nickel electrode shows an irreversible electrochemical behavior of the system Ni(II)/Ni, although the experimental results cannot be interpreted by means of common equations, derived for linear sweep voltammetric responses involving uncomplicated irreversible electrode processes. This may be due to the fact that the solutions do not contain an excess of supporting electrolyte and there is an appreciable migration contribution. In addition, our findings confirm previously developed concept according to that diffusion in ionic liquids disobeys the Stokes–Einstein equation and the transport behavior in ionic liquids cannot be described in terms of "classical" model of diffusion. The activation energy of the charge transfer for the reaction Ni(II) + 2e − → Ni in ethaline has been determined at constant values of electrode potential (the so-called formal activation energy).